2019
DOI: 10.1002/1873-3468.13505
|View full text |Cite
|
Sign up to set email alerts
|

High glucose increases miR‐214 to power a feedback loop involving PTEN and the Akt/mTORC1 signaling axis

Abstract: The mechanism of PTEN repression by high glucose in diabetic nephropathy is not known. Using proximal tubular cells, we show that inhibition of PI3 kinase/Akt and their inactive enzymes prevents high glucose‐induced PTEN downregulation. Similarly, rapamycin (Rapa) and shRaptor block suppression of PTEN by high glucose. In contrast, the constitutive activation of Akt and mechanistic target of rapamycin (mTOR)C1 decrease the expression of PTEN, similarly to high glucose. Remarkably, PI3 kinase/Akt/mTORC1 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…Many studies on kidney-related diseases, such as diabetic nephropathy and acute kidney injury models, have revealed the role of miR-214 [9,35,36], but the mechanism of miR-214 in renal interstitial fibrosis has rarely been investigated. According to our research, we confirmed that miR-214-3p levels were upregulated, PTEN expression was decreased in UUO mice, and this effect was related to renal interstitial 11 Oxidative Medicine and Cellular Longevity fibrosis (Figure 1), which was consistent with existing reports [20,37].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on kidney-related diseases, such as diabetic nephropathy and acute kidney injury models, have revealed the role of miR-214 [9,35,36], but the mechanism of miR-214 in renal interstitial fibrosis has rarely been investigated. According to our research, we confirmed that miR-214-3p levels were upregulated, PTEN expression was decreased in UUO mice, and this effect was related to renal interstitial 11 Oxidative Medicine and Cellular Longevity fibrosis (Figure 1), which was consistent with existing reports [20,37].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of variance followed by Tukey's multiple comparison test was used. A p value of < 0.05 was considered as significant (97).…”
Section: Discussionmentioning
confidence: 99%
“…miR-214 functions as a pro-metastatic factor in malignant tumors ( 42 ), and plays a critical role in the migration and invasion of cancer cells ( 43 45 ). The present study identified a potential link between miR-214 and CADM1 in the coordination of metastasis in melanoma.…”
Section: Discussionmentioning
confidence: 99%